2022
DOI: 10.3390/cells11040660
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Experimental Autoimmune Encephalomyelitis with an Inhibitor of Phosphodiesterase-8 (PDE8)

Abstract: After decades of development, inhibitors targeting cyclic nucleotide phosphodiesterases (PDEs) expressed in leukocytes have entered clinical practice for the treatment of inflammatory disorders, with three PDE4 inhibitors being in clinical use as therapeutics for psoriasis, psoriatic arthritis, chronic obstructive pulmonary disease and atopic dermatitis. In contrast, the PDE8 family that is upregulated in pro-inflammatory T cells is a largely unexplored therapeutic target. We have previously demonstrated a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…The indirect effect of rolipram on IL-17 production is thought to be mediated by monocytes' elevated production of IL-27 (Gonzalez-Garcia et al, 2013;Batten et al, 2006;Stumhofer et al, 2006). Previously, it has also been shown that the expression of the cAMP-specific PDE8A is induced in activated T lymphocytes, and inhibition of the complete PDE8 family by PF-04957325 (10 mg/kg) has been shown to suppress neuroinflammation, thereby reducing the inflammatory lesion load in the EAE animal model (Basole et al, 2022;Glavas et al, 2001). The therapeutic potential of the cAMP-specific PDE4, PDE7 and PDE8 inhibitors highlights the crucial role of cAMP in modulating the anti-inflammatory responses.…”
Section: Fig 4 (Continued)mentioning
confidence: 99%
“…The indirect effect of rolipram on IL-17 production is thought to be mediated by monocytes' elevated production of IL-27 (Gonzalez-Garcia et al, 2013;Batten et al, 2006;Stumhofer et al, 2006). Previously, it has also been shown that the expression of the cAMP-specific PDE8A is induced in activated T lymphocytes, and inhibition of the complete PDE8 family by PF-04957325 (10 mg/kg) has been shown to suppress neuroinflammation, thereby reducing the inflammatory lesion load in the EAE animal model (Basole et al, 2022;Glavas et al, 2001). The therapeutic potential of the cAMP-specific PDE4, PDE7 and PDE8 inhibitors highlights the crucial role of cAMP in modulating the anti-inflammatory responses.…”
Section: Fig 4 (Continued)mentioning
confidence: 99%
“…We next turned our attention to phosphodiesterase 8A (PDE8A), a selective cAMP phosphodiesterase [32] that was also identified as a possible FAK substrate in our phosphoproteomic study at position Y315 ( Figure 1d ). GloSensor Saos2 cells were treated with the selective PDE8A inhibitor PF04957325 [33] ± isoproterenol or PTH. Both basal and ligand-stimulated cAMP levels were increased by PDE8A inhibitor treatment ( Figure 6a ).…”
Section: Resultsmentioning
confidence: 99%
“…The research conducted over the years focusing on the role of PDE8 on T-cell function was reviewed more in detail recently (45). Notably, the PDE8 inhibitor PF-04957325 is able to reduce the inflammatory lesion formation in the central nervous system in the experimental autoimmune encephalomyelitis (EAE) mouse model for multiple sclerosis (46). Table 1 summarizes previous findings about PDE expression and regulation during T cell activation.…”
Section: Pde8mentioning
confidence: 99%